Inovasi media pembelajaran halal berbasis kartu kuartet: Systematic literature review - Didik Darmansyah; Neneng Windayani; Ateng Supriyatna (Nur Science Institute, 2026)
Quartet card-based learning media has emerged as a promising game-based approach for science and halal education, yet its application in halal science education remains insufficiently synthesized. This systematic literature review (SLR) followed PRISMA 2020 guidelines and reviewed 35 peer-reviewed articles (2021–2026) selected from 1,847 records across major academic databases. The synthesis identified five themes: educational card game design, learning effectiveness, halal literacy integration, student engagement, and media assessment. Findings indicate that quartet cards improve student engagement (mean effect size d = 0.71), halal conceptual understanding, and science process skills, particularly when integrated with inquiry-based learning and validated content. However, significant gaps remain, including limited longitudinal research, scarce studies in formal secondary-level halal science education (Tadris IPA), and the absence of standardized assessment instruments. This review proposes the Halal Science Game-Based Learning Framework (HS-GBLF) as a theoretical model integrating constructivist learning, game-based pedagogy, and halal literacy competencies.